Study on Yield Gap and Prioritization of Castor production Constraints for semi-arid regionin Gujarat - A.K. Rai, S. Khajuria, Kanak Lata, Rajkumar and J.K. Jadav, (Indian Journal of Extension Education, 2018)
Castor (Ricinuscommunis L.) is as one of the most important oil crops of the Panchmahal district of Gujarat.However, its productivity of castor in the district is very low. Attempts are made to improve productivity andto increase area under castor by adopting HYVs. In order to compare conventional castorvarieties withHYVs,75 front line demonstrations were carried out in systematic manner on farmers’ field to show the worth of aHYVsin comparison to local varietiesand thereby convincing farmers about potentialities of improvedproduction management practices of castor for further adoption, involving feasible and effective scientificpackage of practices. The demonstrations clearly showed enhancement of productivity, at the same time areaunder castor cultivation was also noticed to be enhanced. The yield was found to be increase from 1980kg/hain local varieties to 2990kg/ha in demonstrations. Similarly, the benefit cost ratio for HYVswas found toincrease to 3.4 as compared to local varieties (2.5). The economic and benefit cost ratio can be further improvedto 3.8 by giving slightly higher inputs for cultivation and marketing. The impact of FLDs was analyzed whichshowed improvement of knowledge and satisfaction of farmers as the main reason for mass scale adoption.